Respuestas

2012-05-03T17:33:37+02:00

buenos dias.8x-(-x+9)=-2-2x
                  8x+x+2x=-2-9
                  11x=-11
                  x=-11/11
                  x=-1
coprobacion:                          8(-1)-(-(-1)+9)=-2-2(-1)
                                            8(-1)+(-1)+2(-1)=-2-9
                                            11(-1)=-11
                                            -1=-11/11
                                             -1=-1 

2012-05-03T17:48:44+02:00

8(x+9)= -2 -2x

semultiplica el 8 por lo de el parentesis:

8x+72=-2 -2x

se pasan los nº de x a un lado y los numeros sin x al otro cambiando de signo:

8x+2x = -2 -72

10x = -74

x= -74/10

x = -7,4